Effects of resilience on anxiety and stress in tertiary students - Garcia-Castillo, Flor Yessenia (2024)
Objective. To identify the correlation between resilience, anxiety, and stress in adolescents. Methods. Data were obtained from a sample of 289 high school students, both males and females, aged between 11 and 18 years. The study followed a non-experimental, cross-sectional, correlational design with a quantitative approach. Results. The findings revealed that the model presented adequate ft indices: CFI = .93, TLI = .92, RMSEA = .06, and SRMR = .05. Additionally, the model showed that resilience negatively influenced anxiety (B = -0.10) and had a very low positive influence on stress (B = 0.03). Furthermore, these findings highlight the importance of considering resilience-evaluated through family interaction, connection with others, and individual skills-as it demonstrates a significant influence. Conclusions. The results indicate that resilience acts as a protective factor against anxiety, reducing its impact, while its influence on stress is positive but minimal.